Contrasting influences of two dominant plants, Dasiphora fruticosa and Ligularia virguarea, on aboveground and belowground communities in an alpine meadow - Song, Hongxian; Liu, Ziyang; Cui, Hanwen; Chen, Jingwei; Chen, Shuyan; Gao, Haining; Yang, Xiaoli; Wang, Yajun; Wang, Jiajia; Liu, Kun; Xiao, Sa; An, Lizhe; et al. (Frontiers in Microbiology, 2023)
Soil organisms are abundant, phylogenetically and functionally diverse, and interact to catalyse and regulate critical soil processes. Understanding what structures belowground communities is therefore fundamental to gaining insight into ecosystem functioning. Dominant plants have been shown to influence belowground communities both directly and indirectly through changes in abiotic and biotic factors. In a field study, we compared the effects of a dominant allelopathic plant, Ligularia virgaurea, and a dominant facilitative plant, Dasiphora fruticosa, on understory plant, soil microbial and nematode community composition in an alpine meadow on the Tibetan plateau. Dasiphora fruticosa was associated with changes in edaphic variables (total nitrogen, soil organic carbon, pH and ammonium), understory plant and soil bacterial communities, whereas Ligularia virguarea was associated with increased soil ammonium content and soil fungal richness relative to dominant plant-free control plots. Moreover, nematode richness was significantly greater under D. fruticosa, with no change in nematode community composition. By contrast, nematode richness under Ligularia virgaurea was similar to that of dominant plant-free control plots, but nematode community composition differed from the control. Piecewise structural equation modelling suggested that the effects of both plants were predominantly direct rather than mediated by indirect pathways despite the observed effects on understory plant communities, soil properties and microbial assemblages. Our results highlight the importance of plants in determining soil communities and provide new insight to disentangle the complex above- and belowground linkages.